2021
DOI: 10.3389/fphar.2021.487316
|View full text |Cite
|
Sign up to set email alerts
|

Doubling the Dose of Bevacizumab Beyond Progression in Metastatic Colorectal Cancer–the Experience of a Tertiary Cancer Center

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer in Europe, with an annual increase in incidence ranging between 0.4 and 3.6% in various countries. Although the development of CRC was extensively studied, limited number of new therapies were developed in the last few years. Bevacizumab is frequently used as first- and second-line therapy for management of metastatic CRC (mCRC). The aim of this study is to present our experience with using bevacizumab beyond disease progression at different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The last cardiovascular adverse event that could happen is hypertension, which, some studies in this systematic review reported that hypertension was a significant side effect caused by bevacizumab toxicity 12 , 13 , 16 , 20 . On the other hand, a gastrointestinal adverse event caused by bevacizumab is GIT perforation 8 , 20 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The last cardiovascular adverse event that could happen is hypertension, which, some studies in this systematic review reported that hypertension was a significant side effect caused by bevacizumab toxicity 12 , 13 , 16 , 20 . On the other hand, a gastrointestinal adverse event caused by bevacizumab is GIT perforation 8 , 20 .…”
Section: Discussionmentioning
confidence: 84%
“…The study by Bencsikova and Vallerio reported that thromboembolic event often happen in CRC patients receiving bevacizumab. On the other hand, studies conducted by Căinap, Bennouna, and Tsai reported that the thromboembolic event was minimal 8 , 13 , 14 , 19 , 20 . Meanwhile, a study by Kapelakis showed that people with past thromboembolic event belong to a high risk group of taking bevacizumab, so it should be administered carefully 6 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations